Acoustofluidic closed-loop control of microparticles and cells using standing surface acoustic waves - Nguyen, Tan Dai (2022)
Precise, automatic and reliable position control of micro-objects such as single particles, biological cells or bio-organisms is critical for applications in biotechnology and tissue engineering. However, conventional acoustofluidic techniques generally lack reliability and automation capability thus are often incapable of building an efficient and automated system where the biological cells need to be precisely manipulated in three dimensions (3D). To overcome these limitations, we developed an acoustofluidic closed-loop control system which is combined with computer vision techniques and standing surface acoustic waves (SSAWs) to implement selective, automatic and precise position control of an object, such as a single cell or microparticle in a microfluidic chamber. Position of the object is in situ extracted from living images that are captured from a video camera. By utilizing the closed-loop control strategy, the object is precisely moved to the desired location in 3D patterns or along designed trajectories by manipulating the phase angle and power signal of the SSAWs. Controlling of breast cancer cells has been conducted to verify the principle and biocompatibility of the control system. This system could be employed to build an automatic system for cell analysis, cell isolation, self-assembling of materials into complex microstructures, or lab-on-chip and organ-on-chip applications.